2022
DOI: 10.1002/pc.26755
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of cellulose nanocrystals from red banana peduncle agro‐waste and application in environmentally friendly biocomposite film

Abstract: The agricultural waste dumped onto the land is creating an environmental problem. The conversion of those easily available agro-wastes into value-added nano reinforcement materials for biopolymers is an alternative method of waste utilization and minimization. In the current study, the red banana peduncle (RBP) waste was used as a precursor in the extraction of carboxylated cellulose nanocrystals (CCNCs) by alkalization, acidified chlorination citric acid hydrolysis, as well as the assessment of its reinforcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Notably, the dimensions are significantly smaller than the size of an empty fruit bunch (EFB) (17.85 nm) [ 68 ] and waste paper (20–40 nm) [ 41 ]. Additionally, AFM was used as a reference technique for evaluating the morphology and size of the nanocellulose [ 69 ]. The AFM-obtained topography image of CNF reveals a thread structure, consistent with the analysis using TEM.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the dimensions are significantly smaller than the size of an empty fruit bunch (EFB) (17.85 nm) [ 68 ] and waste paper (20–40 nm) [ 41 ]. Additionally, AFM was used as a reference technique for evaluating the morphology and size of the nanocellulose [ 69 ]. The AFM-obtained topography image of CNF reveals a thread structure, consistent with the analysis using TEM.…”
Section: Resultsmentioning
confidence: 99%
“…The findings from the study of Nagarajan K. J. et al revealed similar outcomes; according to their SEM investigation, alkali-treated and bleached fibers are observed to be separated from one another. 51 Rod-like structures with separations are seen in Figure 2B, which ensures that acid hydrolysis breaks the amorphous region in the fibers. 42 The width of MFC is observed to be reduced within the range of 4.62-6.16 μm.…”
Section: Morphological and Elemental Analysismentioning
confidence: 98%
“…Acid hydrolysis is often performed to get cellulose nanocrystals after the alkaline treatment and purification, whereas cellulose nanofibers are also obtained by mechanical treatments ter minating in a high-pressure homogenization procedure 3 . Nanocellulose is often isolated from cellulosic materials using acid hydrolysis and it has been obser ved that some of the cellulose chains are more organized than others, and acids quickly break down the disorganized regions while leaving the more orderly ones intact 17 . Nanocellulose is extracted from lignocellulosic biomass using the two-stage process in which the pretreatment eliminates all of the chemicals that are not cellulosic, such as lignin, hemicellulose, (a) coconut husk, (b) cocoa pod husk, (c) corn cob, (d) ramie fiber, (e) enset fiber, (f) kenaf fiber, (g) rice husk, (h) wheat straw, (i) jute fibers, (j) pineapple waste, (k) date pits, and (l) pea hull Biofuels and biopolymers are two examples of value-added products that may be made from lignocellulosic biomass 12 .…”
Section: Nanocellulose From Agricultural Wastes: Extraction and Appli...mentioning
confidence: 99%
“…Though a variety of acids may be used for acid hydrolysis, sulphuric acid (H 2 SO 4 ) is the most commonly used 21 . Sulphuric acid is often used in acid hydrolysis, the sulphate ions esterify the hydroxyl group, allowing the nanocrystalline cellulose to be successfully par titioned and disseminated as a stable colloid system 17 . The separation of cellulose chains and finally the dissolution of cellulose Fig.…”
Section: Nanocellulose From Agricultural Wastes: Extraction and Appli...mentioning
confidence: 99%
See 1 more Smart Citation